Le marché de l’immeuble à bureaux dans la région de Montréal - Daigneault, André (Assurances)

(untitled) (HEC Montréal, 1984)
Within the last few years, the commercial real estate market in Montreal has changed drastically. Around 1970, there was a vacancy rate of 5%, but the completion of a number of major buildings has now made a large amount of space available. Due to the current situation of the economy, it will be several years before these large buildings, begun one or two years ago and just completed, will be filled. Because of this, the owners are willing to give much more generous leases that they would have a few years ago.